2016
DOI: 10.1111/mam.12074
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian biogeography and the Ebola virus in Africa

Abstract: Ebola virus is responsible for the fatal Ebola virus disease (EVD). Identifying the distribution area of the Ebola virus is crucial for understanding the risk factors conditioning the emergence of new EVD cases. Existing distribution models have underrepresented the potential contribution that reservoir species and vulnerable species make in sustaining the presence of the virus. In this paper, we map favourable areas for Ebola virus in Africa according to environmental and zoogeographical descriptors, independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 59 publications
5
59
0
1
Order By: Relevance
“…Mammalian chorotypes in Africa were employed as surrogates of the types of distributions shown by reservoirs and any wildlife species implicated in the virus spillover cycle. Olivero et al (2017a) found that a model based on a number of diversity patterns, each one associated with a different mammalian chorotype, defined favourable areas for the presence of Ebola virus with higher accuracy than did a model based on environmental variables alone (i.e. climate, forest type), concluding that mammalian biogeography contributes significantly to explaining the distribution of Ebola virus in Africa.…”
Section: Chorotypesmentioning
confidence: 93%
See 4 more Smart Citations
“…Mammalian chorotypes in Africa were employed as surrogates of the types of distributions shown by reservoirs and any wildlife species implicated in the virus spillover cycle. Olivero et al (2017a) found that a model based on a number of diversity patterns, each one associated with a different mammalian chorotype, defined favourable areas for the presence of Ebola virus with higher accuracy than did a model based on environmental variables alone (i.e. climate, forest type), concluding that mammalian biogeography contributes significantly to explaining the distribution of Ebola virus in Africa.…”
Section: Chorotypesmentioning
confidence: 93%
“…Ebola virus, Leroy et al 2004, Groseth et al 2007, Olival and Hayman 2014, imposing restrictions to the selection of host or vector species considered in a model might under-represent the zoological substrate conditioning a pathogen's transmission and distribution (Roche et al 2012). Olivero et al (2017a) thus addressed the mapping of favourable areas for the Ebola virus in the wild by combining two biogeographical approaches: SDM and chorotype analysis. Mammalian chorotypes in Africa were employed as surrogates of the types of distributions shown by reservoirs and any wildlife species implicated in the virus spillover cycle.…”
Section: Chorotypesmentioning
confidence: 99%
See 3 more Smart Citations